2021
DOI: 10.1016/j.apm.2020.07.056
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid approach combining DNS and RANS simulations to quantify uncertainties in turbulence modelling

Abstract: Uncertainty quantification (UQ) has recently become an important part of the design process of countless engineering applications. However, up to now in computational fluid dynamics (CFD) the errors introduced by the turbulent viscosity models in Reynolds-Averaged Navier Stokes (RANS) models have often been neglected in UQ studies. Although Direct Numerical Simulations (DNS) are physically correct, obtaining a large enough set of DNS data for UQ studies is currently computationally intractable.UQ based only on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…The numerical solution of the flow field was obtained by the CFD method based on the fluid's generalized continuity equation and momentum equation. The equations were solved based on the three-dimensional incompressible implicit unsteady model, Reynolds average Navier-Stokes equation [21,22], and turbulence model [23].…”
Section: Governing Equations and Turbulence Modelmentioning
confidence: 99%
“…The numerical solution of the flow field was obtained by the CFD method based on the fluid's generalized continuity equation and momentum equation. The equations were solved based on the three-dimensional incompressible implicit unsteady model, Reynolds average Navier-Stokes equation [21,22], and turbulence model [23].…”
Section: Governing Equations and Turbulence Modelmentioning
confidence: 99%
“…Recently, Voet et al. (2021) compared inverse weighted distance-, PCE- and co-kriging-based MFMs using the data of RANS and DNS for the turbulent flow over a periodic hill, and concluded that the co-kriging model outperforms the others in terms of accuracy. This is the first (and to our knowledge only) study where MFMs have been applied to engineering-relevant RANS and DNS data for the purpose of uncertainty propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Voet et al. (2021) also found that the performance of the co-kriging can deteriorate when there is no significant correlation between the RANS and DNS data and at the same time there is a significant deviation between them. Motivated by this deficiency, we adapt and use the HC-MFM where the discrepancy between the data (and not their correlation) over the space of design parameters is learned using independent Gaussian processes.…”
Section: Introductionmentioning
confidence: 99%
“…The drawback to the method is that it is very computationally expensive, with each simulation typically taking a number of days to run 17 . A number of works in the literature leverage a small set of DNS results with Reynolds-Averaged Navier-Stokes (RANS) simulations, which are less accurate due to simplifications in the turbulence closure but also cheaper to evaluate 18 – 20 . An alternative approach is to use the same model with meshes of varying coarseness in order to create low-fidelity surrogates.…”
Section: Introductionmentioning
confidence: 99%